Penilaian Konsumen Terhadap Produk Susu Cair Pada Susu Ultra Milk Dan Cimory - Stephen Pratama dan Chairy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
With the increasing level of milk consumption in Indonesia, such as Indonesia's population of 252 million, the level of consumption of dairy products will increase the nutritional needs. Ultramilk Milk is the dominant dairy market (40% in Indonesia and milk cimory is a newcomer) Ultramilk survivors using Ultra High Technology (UHT) technology that is more durable milk does not have the required content value whereas milk from cimory uses pasturative milk is milk rich in nutrients can not last long. Any benefits of milk will be mixed to create the best design when you want to make a dairy factory. Characteristics (similarities and differences) Freshness, Nutrition, Brand Image, process and packaging in UltraMilk Milk and Milk Ultramilk cimory is just superior in taste After indicator (0.042 < 0.05) in the Freshness variable. Milk Cimory Milk excels in 23 other indiactors such as ketaduasa, aroma of milk, milk taste, milk color, no impurities, net value information, composition information, calorie information, carbohydrate information, fat information, protein information, vitamin information, mineral information, water content, image, Koorporat image, product image, user image, process temperature, protein content, exposure time, flavor variant, variant size and packaging form with the highest value possessed by kimory milk is protein content in milk beverage in the process. (Pasturation) is also caused by the community has begun to understand and understand that milk pasturization is better in consumption compared to UHT Milk Consumer's assessment of Freshness, Nutrition, Brand Image, Process and packaging on UltraMilk and Cimory Milk is only superior to variable Freshness (Freshness) through the Sense of Milk indicator (4.1504 > 4.0708). Ultra milk is superior to nutrition (nutrition) just about the information Protein is given (4.0354 > 4.0177). For Ultramilk Brand Image has no advantages compared to CimoryMilk In UltraMilk Ultra Milk Processing (Process) also does not have any advantages compared to CimoryMilk. For the Ultramilk Package indicator only superior for the Variable size indicator (3.8053 > 3.7876).